Exogenous Cytokinin Promotes Epipremnum aureum L. Growth through Enhanced Dry Weight Assimilation rather than through Changes in Partitioning - Di Benedetto, Adalberto (2015)
Aims: Benzylaminopurine (BAP) sprays have been shown to increase leaf size and leaf appearance rate, as well as biomass accumulation in pot-grown Epipremnum aureum L. BAP-mediated enhanced growth could either be the consequence of a higher investment of dry weight in leaf area development thus leading to a positive dry weight accumulation feedback, to a promoting effect on dry weight assimilation per unit leaf area. Study Design: A randomized complete block factorial design with three blocks was used. Place and Duration of Study: Two experiments were carried out in a greenhouse at the Faculty of Agronomy, University of Buenos Aires, Argentina (34°28’S) from the 8th September 2007 and 5th September 2008, respectively, to the 12th March 2008 and 11th March 2009 respectively. Methodology: We analyzed the effect of exogenous BAP supplied in different number of applications and at different concentrations under three light intensities, on dry weight accumulation and partitioning in E. aureum grown in pots, in two greenhouse experiments. Results: A single 5mg L-1 BAP application was enough to increase the dry weight accumulation rate in comparison to untreated controls, irrespective of the light intensity. A strong direct relationship between the relative growth rate (RGR) and the net assimilation rate (NAR) were found, while an inverse relationship was observed between RGR and the leaf area ratio (LAR). Even though BAP increased dry weight partitioning to the aerial part, as revealed by shoot vs. root allometric analysis, this did not result in a LAR increase, but rather in higher stem dry weight accumulation, in association with a decrease in the leaf area partitioning coefficient (LAP). NAR promotion by BAP was associated with an increased N content per unit leaf area, rather than with changes in chlorophyll content. Conclusion: Our results on the ornamental shade plant E. aureum also provide information which may help to increase productivity to this crop from a grower perspective.